Implementasi Model Contextual Teaching and Learning (CTL) dalam Meningkatkan Kualitas Pembelajaran Pendidikan Agama Islam (PAI) di SMP Muhammadiyah 9 Kota Bandung - Rafi Ahmad Faqih; Nadhifa Fasha Fauziyyah (STIKes Ibnu Sina Ajibarang, 2025)
One of the main problems in learning today is the low absorption of students because the quality of the learning process has not been able to create a quality learning process. In this case the teacher uses the CTL learning model. The purpose of this study is intended to reveal more deeply related to the implementation of the contextual teaching and learning (CTL) learning model in improving the quality of PAI learning at SMP Muhammadiyah 9 Kota Bandung , with a research fokus. (1) Planning of the Contextual Teaching and Learning (CTL) model in improving the quality of PAI learning at SMP Muhammadiyah 9 Kota Bandung, (2) The quality of PAI learning as the output of the implementation of the Contextual Teaching and Learning (CTL) model at SMP Muhammadiyah 9 Kota Bandung. This research uses a qualitative approach, the type of case study research. Data was collected by means of interviews, observation and documentation. Data analysis was carried out through data reduction, data presentation and conclusion drawing. The research results show that: (1) Planning of the Contextual Teaching and Learning (CTL) Model, there are three stages; first, introduction: KD suitability with methods, materials and models, choosing learning media and learning resources. second, implementation: the student center learning process through the stages of constructivism, inquiry, questening, learning community, modeling, reflection, authentic assessment. third, the teacher evaluates the students through authentic assessment. (2) The quality of PAI learning as the output of the implementation of the Contextual Teaching and Learning (CTL) model at SMP Muhammadiyah 9 Kota Bandung. First, teacher learning behavior (building students' positive attitudes towards learning). Second, the behavior and impact of student learning (able and willing to expand knowledge of skills and fortify their attitudes). Third, the learning climate (a climate that is conducive to the development and improvement of curious learning activities). Fourth, learning materials (there is an adjustment between the breadth and depth of the material and the time available). Fifth, learning media (able to improve student learning experience).